Measurement of Small Defect Testing Accuracy in Additive Manufacturing Alloy Using Industrial CT Method. Issue 1 (March 2021) - Guo, Zhimin; Ni, Peijun; Dai, Yuelai; Zhang, Weiguo; Huang, Kuidong
Abstract: This article is based on the application of industrial CT testing in additive manufacturing parts. Based on the existing industrial X-ray CT inspection equipment, it aims to solve the problem of identifying small defects under the uncertainty of test results. Under the premise of removing artifacts, this paper studies the measurement methods of small defects, and analyzes the uncertainty of the test results by designing a comparison test block. This paper combines theoretical analysis and experimental research, and compares the test results with the half-width method to study the accuracy of the test method. In order to improve the accuracy of industrial CT quantitative non-destructive detection of small defects, this paper closely studies the engineering application and combines the practical application of industrial CT to solve the basic problems of key research work.